2019
DOI: 10.14814/phy2.13997
|View full text |Cite
|
Sign up to set email alerts
|

Area under the curve analysis of blood pressure reveals increased spontaneous locomotor activity in SPAK knock-in mice: relevance for hypotension induced by SPAK inhibition?

Abstract: SPAK (Ste20/SPS1‐related proline/alanine‐rich kinase) has been recently identified as a protein kinase which targets the electroneutral cation‐coupled chloride cotransporters and it stands out as a target for inhibition in novel anti‐hypertensive agents. From this prospective, any information about physiological consequences of SPAK inhibition would be useful to better understand the efficacy and potential adverse effects of the SPAK‐based anti‐hypertensive therapy. Radiotelemetry was employed to continuously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…The increase is a consequence of the 150 mmHg of perfusion pressure employed during fixation, which was chosen to increase the reliability of the initial flushing step to remove blood. While this is well above resting blood pressure, it represents the upper end of blood pressure during physical activity (Adlam et al, 2011; Burgess et al, 2019) and is in keeping with or lower than perfusion pressures typically used in vascular casting (Chugh et al, 2009; Ghanavati et al, 2014; Epah et al, 2018).
Fig.
…”
Section: Resultsmentioning
confidence: 97%
“…The increase is a consequence of the 150 mmHg of perfusion pressure employed during fixation, which was chosen to increase the reliability of the initial flushing step to remove blood. While this is well above resting blood pressure, it represents the upper end of blood pressure during physical activity (Adlam et al, 2011; Burgess et al, 2019) and is in keeping with or lower than perfusion pressures typically used in vascular casting (Chugh et al, 2009; Ghanavati et al, 2014; Epah et al, 2018).
Fig.
…”
Section: Resultsmentioning
confidence: 97%
“…The molecular mechanism by which WNKs regulate blood pressure was discovered when it was reported that WNKs bind and phosphorylate both Ste20-related proline–alanine-rich kinase (SPAK) and oxidative stress-responsive gene 1 (OSR1) thus inducing their activation 20 , 21 , 22 , 23 . Furthermore, mice with defected SPAK and OSR1 had reduced baseline blood pressure significantly 24 , 25 , 26 , 27 , 28 . Increased phosphorylated NCC was observed in cells overexpressing SPAK 29 .…”
Section: Regulation Of the Nccmentioning
confidence: 97%
“…The built logistic model assures that any increase in area under curve leads to an increase in cardiovascular risk. Previous studies [13][14][15][16][17] rarely prove the relationship between the electromagnetic transmission coe cient waveforms and blood pressure. However, subtle variations in the morphology of transmission coe cient waveforms, presented in this study, appear correlated to the pressure imposed by blood ow on the walls of blood vessels as shown in Fig.…”
Section: Proposed Bp Estimation Algorithmmentioning
confidence: 99%